2022
DOI: 10.1111/jce.15548
|View full text |Cite
|
Sign up to set email alerts
|

Novel computed tomography angiography‐based sizing methodology for WATCHMAN FLX device in left atrial appendage closure

Abstract: Background While there is recent data suggesting an advantage of computed tomography angiography (CTA) over transesophageal echocardiography (TEE) for preprocedural left atrial appendage closure (LAAC) planning, there is limited published experience for sizing strategies. Device sizing for LAAC may be challenging and noninvasive algorithms that improve this selection process are warranted. Objectives We sought to evaluate the safety and the feasibility for the implementation of a novel CTA‐based sizing methodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…(Watchman FLX), mean 1.0 devices/case and 100% procedural success rate using preoperative CMR with intraoperative ICE in a 10 patient series by Dallan et al. (Watchman FLX and Amulet), this study demonstrated similar outcomes with mean 1.2 devices/case and 96% procedural success rate using preoperative CMR with intraoperative TEE and/or ICE (Watchman FLX and Amulet) 6,18,19 . Overall, the use of preoperative CMR in this study resulted in an acceptable procedural success rate both immediately and on short‐term follow‐up.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…(Watchman FLX), mean 1.0 devices/case and 100% procedural success rate using preoperative CMR with intraoperative ICE in a 10 patient series by Dallan et al. (Watchman FLX and Amulet), this study demonstrated similar outcomes with mean 1.2 devices/case and 96% procedural success rate using preoperative CMR with intraoperative TEE and/or ICE (Watchman FLX and Amulet) 6,18,19 . Overall, the use of preoperative CMR in this study resulted in an acceptable procedural success rate both immediately and on short‐term follow‐up.…”
Section: Discussionsupporting
confidence: 71%
“…17 procedural success rate using preoperative CMR with intraoperative TEE and/or ICE (Watchman FLX and Amulet). 6,18,19 Overall, the use of preoperative CMR in this study resulted in an acceptable procedural success rate both immediately and on short-term follow-up.…”
Section: Discussionmentioning
confidence: 68%
“…In this issue of the Journal, Hokken et al 3 provide clinical evidence that CT‐derived computer simulation can improve TAVR outcomes. In a multicenter, prospective observational study of TAVR in patients with challenging anatomy, they found that the HEARTguide computer simulation software (FEops) changed the procedural plan in 35% of patients, including changes in valve size and target implantation depth.…”
Section: Interventional Procedures Preprocedures Simulationsmentioning
confidence: 99%
“…The TruPlan simulation software for WATCHMAN FLX procedure planning (Boston Scientific) has been shown to reduce the number of deployment attempts as well as the risk of peri-procedural adverse events. 3 Additionally, intracardiac echocardiography (ICE) imaging guidance for LAAO has become more Expert Article Analysis for: Clinical value of CT-derived simulations of transcatheter-aortic-valve-implantation in challenging anatomies the PRECISE-TAVI trial…”
mentioning
confidence: 99%
“…2 Planning for LAAO procedure includes utilization of cardiac imaging including transesophageal echocardiography (TEE), cardiac computed tomography angiography (CCTA), and cardiac magnetic resonance imaging to rule out LAA thrombus, LAA sizing, and defining the optimal transseptal access and landing zone of LAAO. 3,4 3-D CCTA will define the complex anatomy LAA anatomy than TEE or intracardiac echocardiogram (ICE) including multiple lobes, hidden lobes, and acute angle of LAA neck and improve the LAAO procedure outcome. Fusion technology of integration fluoroscopy into 3D-multidetector computed tomography (3D-MDCT) has been utilized in the LAAO procedure work-flow with an improvement of the LAAO procedure outcome [5][6][7] In this issue of Journal of Cardiovascular Electrophysiology, There is a reasonable explanation for the difference between the current study and previous studies clinical and procedure outcomes of LAAO for Watchman device with 3D-MDCT fluoroscopy fusion technology.…”
mentioning
confidence: 99%